RISK MITIGATION FOR SMALL AND MEDIUM-SIZED ENTERPRISES (SMES) IN THE MIDDLE OF VOLATILITY IN THE WORLD’S ECONOMY CONDITION - Gresika Bunga Sylvana (OISAA, 2021)
ABSTRACT Indonesia's economic growth in the first quarter of 2020 of 2.97% was released by the Central Statistics Agency (BPS). It is undeniable, that number is the lowest growth rate in the last 19 years. We understand that the economic disruption caused by the COVID-19 pandemic did occur in various parts of the world. A significant economic slowdown is a big task for many national leaders. Some world economic experts even mention that the disruption of the economy due to this pandemic can resemble the effects of the Great Depression of 1930 ago. If we review the impact of the COVID-19 pandemic which has caused extraordinary disruption in the economic field, it is seen that Micro, Small, and Medium Enterprises (MSMEs) are a sector that is quite severe. Basically, the concept of risk management is not commonly used in SMEs business processes. This is because, in general, the resources owned by SMEs are quite limited. However, in this paper I want to illustrate at least there are simple concepts that can be applied by SMEs.